2010
DOI: 10.1186/1742-2094-7-68
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 4, a novel transcription factor regulates microglial activation and subsequent neuroinflammation

Abstract: BackgroundActivation of microglia, the resident macrophages of the central nervous system (CNS), is the hallmark of neuroinflammation in neurodegenerative diseases and other pathological conditions associated with CNS infection. The activation of microglia is often associated with bystander neuronal death. Nuclear factor-κB (NF-κB) is one of the important transcription factors known to be associated with microglial activation which upregulates the expression of inducible nitric oxide synthase (iNOS), cyclooxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 65 publications
6
105
1
Order By: Relevance
“…Similar results were found with 2 commercial antibodies. A similar expression pattern of KLF4 in both the nucleus and cytoplasm has been reported in other tissues (22,23). It has been suggested that KLF4 is stored in the cytoplasm and translocates to the nucleus after stimulation (23), which would explain why both nuclear and cytoplasmic staining were observed.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results were found with 2 commercial antibodies. A similar expression pattern of KLF4 in both the nucleus and cytoplasm has been reported in other tissues (22,23). It has been suggested that KLF4 is stored in the cytoplasm and translocates to the nucleus after stimulation (23), which would explain why both nuclear and cytoplasmic staining were observed.…”
Section: Discussionsupporting
confidence: 77%
“…Our studies also provide insights regarding discrepant observations in the literature regarding the kinetics of KLF4 expression and its targets in response to proinflammatory stimuli. It is likely that (a) idiosyncrasies of various cell lines employed (e.g., J774a, THP-1, RAW, and BV-2) and (b) differences in the concentration (ranging from 10 ng/ml to 1,000 ng/ml) and source of LPS employed (e.g., E. coli, Porphyromonas gingivalis, and Salmonella enterica) may account for many of the disparate results seen among various studies (23)(24)(25)(26)(27)(28). For example, several studies in cell lines and/or primary cells have reported an increase in KLF4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have reported that KLF4 is expressed in a stage-specific pattern during myelopoiesis and functions to promote monocyte differentiation (21,22). While several studies have evaluated the role of KLF4 in macrophage cell lines (23)(24)(25)(26)(27)(28), the physiologic role of myeloid KLF4 in vivo has not been elucidated. Given the important roles of the KLF family members in cellular differentiation, we hypothesized that KLF4 might be involved in the transcriptional control of macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The BV-2 cell line (a mouse microglia cell line) was provided by Steve Levison, University of Medicine and Dentistry, New Jersey, USA. BV-2 cells were grown at 37°C in Dulbecco's modified Eagle's medium (DMEM) supplemented with 5% sodium bicarbonate (NaHCO 3 ), 10% FBS, 100 U/ml penicillin, and 100 g/ml streptomycin, as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…Primary microglia cells were isolated from BALB/c mouse pups of either sex (postnatal days 0 to 2), as reported previously (25). Briefly, the whole brain cortex was dissected from the mouse brain, and the meninges were removed under a dissecting microscope.…”
Section: Methodsmentioning
confidence: 99%